Extending a geographical perspective to the study of jurisdictional consistency in sentencing outcomes - Reid, Andrew A. (The British journal of criminology, 2018)
Consistency in sentencing has long been regarded as a fundamental principle of justice. Yet despite its universal importance, research has been hindered by many theoretical and methodological challenges. This study identifies a new concern with strategies used to measure jurisdictional consistency: direct measures fail to account for sentencing patterns developed at the local level. The objective of this study is to assess the utility of applying a geographical perspective to analyses of sentencing outcomes—one concerned with proportionate comparisons between jurisdictions. This is achieved by proposing a variant of a common metric applied in geographical research: the location quotient. Analyses using the new strategy compare sentence outcomes across provincial/territorial jurisdictions in Canada (2014–15). The technique identifies new patterns of consistency and inconsistency that would otherwise have gone undetected.